Веселые загадки, поговорки, пословицы, скороговорки - Скворцова С. А. (Сказки-Хит, 2010)
Экземпляры: ф.14 (2010) / Инвентарный номер: 46958 / Цена: / Сис.шифр: 82.3(2) / Авт.знак: В 38 / ББК: 82.3(2Рос=Рус)-6